The Effect of pH and Adsorption Time in Fe and Mn Concentration Decreasing using Zeolite in Sungai Enim River at Desa Darmo Tanjung Enim - Purnamasari, Indah (Politeknik Negeri Sriwijaya, 2017)
Water in the river contains metals contaminant such as Fe and Mn. There’s many method that used to reduce heavy metals ions, such as by using adsorption method. This research utilized zeolite as an adsorbent. This research aimed to study the effect of adsorption parameters on the decrease of heavy metal ions adsorbed in zeolite and determine the equilibrium equation of the isotherm adsorption. Water river and zolite are contacted with certain comparisons in the batch column. The variables studied were pH of solution (1, 3, 5, 7, and 9), and adsorption time (10, 20, 30, 40, 50 min),. The results show that zeolite can be used to reduce the heavy metal content of Fe and Mn. The process is best conducted at 30 minutes, in 40 gram adsorbent weight, and pH 7. The zeolite adsorption model of water in river fits well to Langmuir's adsorption Isotherm model in all condition dengan Qm = 2,5 x 10-3 mg/g.